Thinking the Re-Thinking of the World : Decolonial Challenges to the Humanities and Social Sciences from Africa, Asia and the Middle East. - Kresse, Kai. (ZMO-Studien Ser., 2022)
The refereed series ZMO-Studien publishes monographs and edited volumes which mirror the interdisciplinary research programme and approach of the Leibniz-Zentrum Moderner Orient.